Mental simulation and compulsive buying: a multiple mediation model through impulse buying and self-control - Duan, Xiaowei (Frontiers in Psychology, 2025)
This study explores the multiple mediation effects of impulse buying and a self-control failure on the relationship between two types of mental simulation—outcome and process simulation—and compulsive buying. We collected 202 responses using a web-based survey, which were used as a final example. The respondents for this study were recruited through the web-based survey platform Nown Survey. Using structural equation modeling and PROCESS for SPSS (Model 6), we estimated the internal consistency of measurements and tested the established hypotheses. The main findings confirm the distinct impacts of the two types of mental simulation on primary constructs and the multiple mediation effects of impulse buying and self-control failure on the associations between the two types of mental simulation and compulsive buying. Despite the multiple mediating effects of impulse buying and self-control failure between the two types of mental simulation and compulsive buying, process simulation is positively associated with both impulse buying and compulsive buying, while outcome simulation is significantly related only to impulse buying. Our results supplement existing literature by applying new insights into the relationships between mental simulation and compulsive buying. Further, our findings may help marketers to establish strategies based on the divergent roles of the two types of mental simulation to motivate consumers’ purchase behaviors. Finally, the limitations and directions for future research are discussed.